Respostas

2014-02-01T17:09:53-02:00
Δ = b² -4ac
Δ = (-12)² -4 *1 * 27
Δ = 144 -108
Δ = 36
x' = (-b + √∆)/ 2a
(-(-12) + 6)/2 * 1
(12 + 6)/2
18/2
9
x'' = (-b - √∆)/ 2a
(-(-12) - 6)/2 * 1
(12 - 6)/2
6/2
3

S={9,3}
2 3 2
2014-02-01T17:19:18-02:00
Ola, para resolver esta equação você podera utilizar a formula de baskara: 

 b^{2} -4a.c

substituindo: (- 12^{2}) -4.1.27
144-108=36

Agora é só achar as raizes

x= -\frac{b-+ \sqrt{36} }{2.1}
x'=  \frac{12+6}{2} = 9
x''=  \frac{12-6}{2} = 3
As raizes são: 3,9
2 3 2